CONSTITUTIONAL LIMITS ON GOVERNMENT USE OF FACIAL RECOGNITION TECHNOLOGY IN PUBLIC SERVICES AND PUBLIC SECURITY - Wiredarme (Ninety Media Publisher, 2025)
This study aims to examine the constitutional limits of government use of facial recognition technology in public services, public security, and citizen identification. The central issue addressed in this article is the tension between state interests in security and administrative efficiency on the one hand, and the protection of privacy, civil liberties, equality, due process, and constitutional rights on the other. This study employs a qualitative legal research method with a normative-doctrinal approach. The analysis is conducted through statutory, conceptual, and comparative approaches by examining constitutional principles, legal norms, regulatory frameworks, human rights standards, and recent academic literature on facial recognition, biometric governance, digital identity, and public-sector surveillance. The findings show that facial recognition is not merely a technical instrument, but a form of constitutional state action because it enables the government to collect, process, store, and act upon citizens’ biometric identity. In public services, the technology may improve verification and administrative efficiency, but it may also create forced consent and exclusion from essential services. In public security, facial recognition may support lawful identification, but it may also enable mass surveillance, chilling effects, discriminatory outcomes, and unchallengeable decisions. This study contributes a constitutional boundary framework based on legality, legitimate aim, necessity, proportionality, transparency, accountability, non-discrimination, meaningful human review, and effective remedy. The study implies that facial recognition may only be constitutionally justified when technological capability remains subject to strict rights-based legal control.